Influencing or Intervention? Impact of Constitutional Court Decisions on the Supreme Court in Indonesia - Dian Agung Wicaksono; Faiz Rahman (The Constitutional Court of the Republic of Indonesia, 2022)
The third amendment of Indonesia’s 1945 Constitution, conducted in 2001, had significant implications for the nation’s judiciary. It transformed the judiciary from a single to a dual structure. Consequently, there are two apexes of the judiciary: the Supreme Court and the Constitutional Court. Furthermore, the establishment of the Constitutional Court divided judicial review authority between the two apex courts. The Constitutional Court can review laws against the Constitution, while the Supreme Court has the power to review whether regulations, made under laws, contradict such laws. Although the Indonesian Constitution provides explicit delineations over the absolute competence of judicial review, the division of judicial review has often triggered tension between the two courts. The Constitution allows the Supreme Court to have additional authorities granted by laws. On the other hand, the Constitutional Court has the power to review any law against the Constitution, including laws related to the Supreme Court. This article seeks to answer the important question of whether the Constitutional Court could influence or intervene in the Supreme Court through judicial review. The authors argue that the duality of judicial review authority unintentionally causes an imbalance in the functional relationship between the two apexes of the judiciary. The main reason is that the Constitutional Court can influence or intervene in the Supreme Court through constitutional review authority. The authors examine two essential aspects of this: (1) the functional implications of duality of judicial review authority; and (2) the implementation of the Constitutional Court’s authority in reviewing laws, especially those closely related to the Supreme Court’s authorities. Various cases are examined to illustrate how the Constitutional Court could directly or indirectly influence the Supreme Courts’ authorities. The Constitutional Court, however, often seems to ‘play safe’ to maintain the judiciary’s imbalanced relationship caused by the dualism of judicial review authority.